Political debates and agricultural policies: Discourse coalitions behind the creation of Brazil's Pronaf. (July 2018) - Ghinoi, Stefano; Wesz Junior, Valdemar João; Piras, Simone
Abstract: The literature on rural development focuses on the socio-economic effects of agricultural support policies; the process of policy design, however, is devoted less attention. Identifying policy coalitions may help provide clarity on the motivations behind a given agricultural support system. Using Discourse Network Analysis, this paper studies the debates preceding the approval of the National Program for Strengthening Family Agriculture (Pronaf) in Brazil in the Nineties. This represented a relevant overturn of the preceding policy framework. Two coalitions that opposed each other have been identified: while large farm business associations favoured measures to enhance productivity, movements comprising of family farmers aimed at introducing credit instruments for small producers. The strong pressure from social movements was key to the adoption of Pronaf. However, findings suggest that the Workers' Party, which found itself in a less conflicting position, played a brokerage role in the negotiation of the final policy package.